Incidence of syphilis infection and syphilis-related care utilization among adolescents and young adults living with HIV. (February 2022) - Bonett, Stephen; Tam, Vicky; Singapur, Anjali; Min, Jungwon; Koenig, Helen C; Wood, Sarah M
Background: Incidence of syphilis has been rising in recent years and disproportionately affects young adults, racial/ethnic minority men, and people living with HIV. This study describes patterns of syphilis infection and syphilis-related care utilization among adolescents and young adults living with HIV (AYALH) in Philadelphia. Methods: We conducted a retrospective cohort study of AYALH receiving care at an adolescent-specialty clinic who received a syphilis test and/or benzathine penicillin for syphilis treatment from 2011 to 2018 ( N = 335). Syphilis incidence rates were calculated by baseline demographic characteristics and by calendar year. Recurrent survival analysis was used to explore how demographic and neighborhood-level factors were associated with incident syphilis and syphilis-related care utilization. Results: Syphilis-related care was provided 145 times and there were 109 episodes of confirmed syphilis among 83 unique participants between 2011 and 2018. The overall syphilis incidence rate was 13.50 (95% CI: 10.9–16.5) cases per hundred person-years. Participants assigned male sex at birth had higher hazards of infection (HR: 6.12, 95% CI: 1.53–24.48), while older participants (HR: 0.64, 95% CI: 0.58–0.72) and those living further from the clinic had lower hazards of infection (HR: 0.97, 95% CI: 0.94–1.00). Race, insurance status, neighborhood diversity index, and neighborhood social disadvantage index were not associated with hazard of infection or syphilis-related care utilization. Conclusions: Our study found high incidence of syphilis infection among a cohort of AYALH. Integrating comprehensive sexually transmitted infection prevention services into HIV care and improving syphilis prevention services in communities with high syphilis rates should be a priority in future intervention work.